Chairing a Session - Savva, Christos S. (My University, 2026)
1. Ensuring speakers are on time and present for the session 2. Introducing the speakers at the beginning of the session 3. Making sure each speaker begins/ends at the time allotted 4. Facilitating Q&A discussion after each presentation, including preparing questions in advance to spark discussion